FEATURES OF TIRING DESTRUCTION OF SLIDING TRIBOSYSTEMS DURING ABRASIVE WEAR - Дворук, В. І. (Proceedings of National Aviation University (archive), 2021)
It is shown that the intrusion destruction of methane under the load of sliding friction in the presence of abrasive between the friction surfaces has a viscous character.